ESTIMATION OF TOTAL FLAVONOID, PHENOLIC CONTENT, AND FREE RADICAL SCAVENGING POTENTIAL OF GLYCYRRHIZA GLABRA ROOT EXTRACT - S, Velvizhi; S, Annapurani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The present study attempts to estimate the total flavonoid and phenolic content and to evaluate the free radical scavenging activity of the roots of Glycyrrhiza glabra Leguminosae family. Methods: The various extracts, namely, petroleum ether, chloroform, ethyl acetate, aqueous, and methanol of G. glabra root were evaluated by 2, 2-diphenyl-1-picryl-hydrazyl (DPPH), hydroxyl radicals, superoxide, 2,2'-azino-bis-3-ethyl benzthiazoline-6-sulphonic acid (ABTS), and non-radicals such as hydrogen peroxide (H2O2) and nitric oxide (NO) and assays. Total flavonoid and phenol contents were estimated as per the standard procedure. Results: The effect of the methanolic extract of G. glabra root was found to be more in scavenging the free radicals such as DPPH, hydroxyl, H2O2, superoxide, NO, and ABTS when compared to other extracts. The presence of flavonoids and phenol in the plant is responsible for the free radical scavenging effects. Conclusion: This in vitro assessment of the antioxidant properties of the various extracts of G. glabra roots validates and confirms its free-radical scavenging activity. Thus, the present data suggest that the G. glabra root extract can be used as a good source of natural antioxidants for health benefits.